1997
DOI: 10.1016/s0006-3495(97)78247-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of collagen fibers. Influence of fibrillar alignment and decorin on mechanical properties

Abstract: Collagen is the primary structural element in extracellular matrices. In the form of fibers it acts to transmit forces, dissipate energy, and prevent premature mechanical failure in normal tissues. Deformation of collagen fibers involves molecular stretching and slippage, fibrillar slippage, and, ultimately, defibrillation. Our laboratory has developed a process for self-assembly of macroscopic collagen fibers that have structures and mechanical properties similar to rat tail tendon fibers. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
319
1
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(336 citation statements)
references
References 41 publications
12
319
1
4
Order By: Relevance
“…These improvements in material behavior with mechanical stimulation have been commonly reported for engineered tissues, and are attributed to improved collagen synthesis and organization [12,[23][24][25]. For example, Pins et al found that greater stretch of self-assembled collagen fibers resulted in both improved collagen fibril alignment as measured by TEM as well as higher tangential elastic moduli [25]. In addition, Garvin et al found that the application of cyclic tensile stretch via the Flexcell system resulted in greater expression of collagen types III and XII, greater expression of prolyl hydroxylase (involved in collagen synthesis), and a measured elevation in ultimate tensile strength [12].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These improvements in material behavior with mechanical stimulation have been commonly reported for engineered tissues, and are attributed to improved collagen synthesis and organization [12,[23][24][25]. For example, Pins et al found that greater stretch of self-assembled collagen fibers resulted in both improved collagen fibril alignment as measured by TEM as well as higher tangential elastic moduli [25]. In addition, Garvin et al found that the application of cyclic tensile stretch via the Flexcell system resulted in greater expression of collagen types III and XII, greater expression of prolyl hydroxylase (involved in collagen synthesis), and a measured elevation in ultimate tensile strength [12].…”
Section: Discussionmentioning
confidence: 66%
“…These improvements in material behavior with mechanical stimulation have been commonly reported for engineered tissues, and are attributed to improved collagen synthesis and organization [12,[23][24][25]. For example, Pins et al found that greater stretch of self-assembled collagen fibers resulted in both improved collagen fibril alignment as measured by TEM as well as higher tangential elastic moduli [25].…”
Section: Discussionmentioning
confidence: 83%
“…During loading of collagen molecules, fibrils, and fibril bundles deform and finally fail by a process termed defibrillation. Up to a strain of 2% (toe region), stretching of the triple helix is the predominant mechanism of deformation [268][269][270][271] and corresponds to the gradual removal of a macroscopic crimp in the collagen fibrils [272][273][274][275][276][277][278][279][280][281]. This macroscopic crimp has been characterised as the shock absorber of tendons that permits non-damaging longitudinal elongation of fibrils within the tissue [261,282].…”
Section: Mechanical Properties Of Tendon Tissuementioning
confidence: 99%
“…At strains beyond 2% strain, the low modulus of the toe region gives rise to the nonlinear heel region, during which reorientation and un-crimping of the collagen fibrils and stretching of the triple helix, the non-helical ends and the cross-links takes place [269,271,283]. When collagen is stretched beyond the heel region, no further extension is possible [259,270,284,285], the wavy pattern is now straightened and cross-links and fibrils start breaking [261]. To-date, advances in chemistry and engineering have made available numerous polymers, cross-linking systems and scaffold fabrication technologies that closely imitate the biomechanical properties of native tendons (Table 3).…”
Section: Mechanical Properties Of Tendon Tissuementioning
confidence: 99%
“…Mechanical properties of collagen fibers and proteoglycan matrix have been reported by several authors [24][25][26][27]. Table 1 shows experimental measurements of mechanical properties of collagen fibers and proteoglycan matrix used in this study [28][29][30]. Experimental measurements of aggregate modulus of articular cartilage in z-h plane have been reported by Schinagle et al [2].…”
Section: Mechanical Properties Of the Transition Zonementioning
confidence: 70%